Aktualisasi Nilai-Nilai Ajaran Islam Rahmatan Lil Alamin di Perguruan Tinggi Umum - Diky Dwi Setiaji; Moh. Novin Herlambang; Ayang Alvin Agachi; Ibnu Ahdiat Miharja; Muhamad Basyrul Muvid (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
Rahmatan Lil 'alamin is a term of the Koran referring to the main purpose of da'wah carried out by the Prophet Muhammad SAW. This term is often used to explain that Islam is a religion of peace, compassion, tolerance, and love of kindness. However, in the Qur'an, the hadith and the history of the da'wah of the Prophet Muhammad and his companions show that not all activities aimed at upholding rahmatan lil' alamin can be presented with peace, compassion, tolerance, and love of kindness, but there is also the concept of jihad, amar ma' Ruf nahi munkar and wala 'with fellow believers. This paper tries to explore the meaning of grace in the Qur'an and how to make it happen with the thematic interpretation method approach. Based on the results of the study, it was found that the meaning of rahmatan lil 'alamin will be realized when there is a balance between hablun minallah and hablun minannas, namely implementing twelve activities related to the hablun minallah relationship and twelve activities related to hablun minannas.